Efeitos da bupropiona sobre o comportamento sexual, parâmetros espermáticos e fertilidade de ratos machos e sobre a contratilidade do ducto epididimático in vitro - Cavariani, Marilia Martins [UNESP] (2013)
Bupropion is a dopamine and norepinephrine reuptake inhibitor with lower effect on the serotonine reuptake widely used as smoking cessation and antidepressant drug. Previously studies showed that the treatment with the norepinephrine uptake blocker sibutramine, that acts increasing the level of this monoamine at the synaptic cleft impaired the sperm quality and fertility of the animals treated with this drug. Bupropion influences some sexual functions as ejaculation and arousal however, to our knowledge, there is no study investigating the effects of bupropion on human or animals model sperm quality. In this context, the present study investigated the effects of bupropion on sexual behavior, sperm parameters and fertility of male rats as well as its influence on epididymal duct contraction in vitro. For this, 27 male rats (90 days) were randomly allocated into three experimental groups that received 15 mg/kg of bupropion (BPP15, n=9), 30 mg/kg of bupropion (BPP30) and distillate water (vehicle, VEH, n=9) orally during 30 days. At the end of the treatment the animals were killed and his reproductive organs (testis, epididymis, prostate, full and empty seminal vesicle) were weighted. The levels of testosterone, luteinizing hormone and follicle stimulating hormone serum were determinate by radioimmunoassay and the right testis and epididymis were collected and processed to sperm count, daily sperm production and determination of sperm transit time trough epididymis. Furthermore, spermatozoa collected by the right epididymal cauda were used to analysis of sperm motility and morphology. In a second stage of this study 30 animals (n=10/experimental group), allocated and treated as describe previously, were used to analysis of male sexual behavior and fertility after natural matting. At the least stage of the study 18 animals (n=6/experimental group) were used to evaluating the effects of the treatment with ...